Analysis of the Public Tender FTIC-LP-038-2020 of the Ministry of Information and Communication Technologies (2022)
The Colombian state, in search of fulfilling its purposes, meeting the needs of citizens and guaranteeing the principles, duties and rights that the Political Constitution of Colombia of 1991 deals with in its article 2, through public contracting which is It is regulated in Law 80 of 1993 and in compliance with the principles of state contracting, to guarantee that the processes are transparent, timely and conditions of equality and objective selection are guaranteed; which must be applied in the contractual processes carried out by the different public entities for the acquisition of goods and services which are essential for the fulfillment of their mission. The Ministry of Information Technologies and Communications to comply with the development plan and the public policy of digital government, in search of continuous improvement and in order to provide a better quality of life to the inhabitants of the 32 departments of the country, mainly benefiting schools and colleges in rural areas through digital transformation and meeting the needs of users to access the internet service in 2020, the Public Tender FTIC-LP-038-2020 of 2020 was carried out for a total amount of $2,138,117,270,447, in which there was an irregularity due to mishandling of the advance with an economic loss of $70,243,279,599; and the violation of several of the principles of state contracting and as a consequence the most vulnerable populations were affected and primarily the students of the most remote populations who did not have the internet service to receive their virtual classes, taking into account that This year the pandemic began, which lasted approximately 2 years, which meant that students could not receive their classes in a timely manner, thus violating their right to education.